Anteseden Penurunan Penjualan Produk Kosmetik GRS Rendy - Santoso, Kevin Cahya; Sutanto, Eddy Madiono (Jurnal Bisnis dan Kewirausahaan, 2023)
This research was conducted to determine the antecedent factors that led to decreased sales of cosmetic products by GRS Rendy Company. Data collection by distributing questionnaires to company owners and consumers aged 17 years and over and having purchased at least once. The results of the research questionnaire from the owner stated that it was true that the sales of cosmetic products had decreased over the last five months, and the number of consumers had also decreased during that time. The respondents were 111 people. The data is then processed using factor analysis techniques. This study found two factors causing a decrease in the sales of cosmetic products at GRS Rendy: weak product features and innovation and attractiveness in markets that are less able to compete